Montmorillonite embedded electrospun PVdF–HFP nanocomposite membrane electrolyte for Li-ion capacitors. (December 2016) - Solarajan, Arun Kumar; Murugadoss, Vignesh; Angaiah, Subramania
Graphical abstract: Highlights: Preparation of MMT incorporated PVdF/HFP membranes by electrospinning method. Incorporation of MMT increased the thermal stability and mechanical strength. The Li-ion capacitor with esCPME (5 wt% MMT) exhibits the enhanced performance. Abstract: The electrospun poly(vinylidene fluoride-co-hexafluoropropylene)/montmorillonite nanofibrous composite membranes (esCPMs) were prepared by electrospinning technique using a mixture of different amounts of montmorillonite (0, 3, 5, 7 and 10 wt%) into 16 wt% of PVDFHFP polymer solution in 7:3 wt% of acetone and dimethylacetamide as the solvent. The effect of montmorillonite (MMT) on electrospun PVdF–HFP membrane has been studied by XRD, DSC, TGA and tensile strength analysis. The average diameter of the electrospun nanofibrous composite membrane was about ∼400 nm. The physical properties such as porosity, electrolyte uptake and mechanical strength of the electrospun nanofibrous composite membrane were studied in detail. The ionic conductivity and electrochemical stability windows of the electrospun nanofibrous composite membrane containing 1 M LiPF6 in EC:DMC (1:1, v/v%) as an electrolyte (esCPME) were studied by AC-impedance and linear sweep voltammetry studies, respectively. It is found that electrospun PVDF–HFP/MMT nanofibrous composite membrane obtained using 5 wt% MMT has a higher porosity, electrolyte uptake, ionic conductivity and electrochemical stability window than the other nanofibrous composite membrane systems and are found to be 88.1%, 428%, 2.330 × 10 −3  S/cm and 3.1 V, respectively. Finally, the charge–discharge studies were carried out by fabricating a prototype Li-ion supercapacitor by sandwiching PVDF–HFP/MMT (5 wt%) nanofibrous composite membrane electrolyte in between a carbon anode and LiCo0.2 Mn1.8 O4 cathode. It showed higher specific discharge capacitance and good compatibility with electrode materials suggesting that the electrospun PVdF–HFP/MMT nanofibrous composite membrane electrolyte could be used as the best candidate for high performance Li-ion capacitors.